The Extent of Future Thinking Skills Inclusion in Digital Skills Course for the Fourth Grade of Elementary Schools in the Kingdom of Saudi Arabia - Alnufaei, Amani Muneer; Almohammadi, Najwa Atyan (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to know the extent to which future thinking skills are included in digital skills books for the fourth grade of primary school in the Kingdom of Saudi Arabia. To achieve the study objectives, the study followed the descriptive analytical approach using the content analysis method to suit the nature of the study, as the content of the digital skills course taught by fourth grade students in the primary stage was analyzed for the three semesters, for the academic year 1445 AH - 2023 AD edition, using a content analysis card that included (4) main skills followed by (24) indicators to measure performance distributed into four main skills for future thinking skills, namely: anticipation skill, prediction skill, visualization skill, and problem solving skill. The results showed that the inclusion of future thinking skills in the digital skills course for the fourth grade of primary school in the Kingdom of Saudi Arabia was at a low rate of (25%); In light of the results, the study recommended developing digital skills courses for the fourth grade of primary school in the Kingdom of Saudi Arabia in light of future thinking skills due to the importance of these skills in preparing an individual capable of facing and overcoming the challenges that may face him in the future.